The analysis of violation features of hypo-curation type pharmacological compliance in patients with type 2 diabetes mellitus - Tkachenko, Olga (ScienceRise: Medical Science, 2017)
Aim. To determine features and triggers of hypo-curation type pharmacological compliance violations in patients with type 2 diabetes. Materials and methods. 486 patients with type 2 diabetes mellitus were examined on the clinical basis of therapy, clinical pharmacology and endocrinology department of the State Institution “Zaporizhzhia medical academy of post-graduate education of Ministry of health of Ukraine”. The patients were divided in two groups depending on type 2 diabetes severity levels: 312 patients with DM type 2 of moderate severity formed the first clinical group; the other 174 patients with severe DM type 2 formed the second clinical group. Anamnesis and clinical examination, clinical and psychopathological, and statistical methods were used. Results. In result of research, specific features and triggers of hypo-curation type pharmacological compliance violations in patients with type 2 diabetes were determined. It was found, that pharmacological compliance violations in patients with type 2 diabetes were observed in 76.34 % of cases, in 66.87 % among them hypo-curation type pharmacological compliance violations were identified. Structural components of hypo-curation type pharmacological compliance were determined. Features of carbohydrate metabolism disorders in patients with hypo-curation type pharmacological compliance violations were observed. Incompliance factors as triggers of hypo-curation type pharmacological compliance violations in patients with type 2 diabetes were selected; they were classified, and their correlation was determined. Conclusion. The notion about hypo-curation type pharmacological compliance violations in patients with type 2 diabetes was expanded. That eliminated gaps in scientific knowledge about pharmacological compliance violations in patients with type 2 diabetes